Mídias científicas fora do padrão: Como a diversidade pode impactar a visão e identificação científica - Ferreira, João Vítor dos Santos (Universidade Federal de São Carlos, 2024)
The purpose of this paper is to discuss and characterize the different contributions that the dissemination carried out on social media by alternative scientific networks can make to the social conception of science and scientists, contributing to aspects such as representativeness, anti-racism and ancestry. These alternative networks are made up of black people, indigenous people, trans people, women and minority groups who go against the standard notion of science communicators. In this context, we intend to discuss how these contributions confront image control, an idea proposed by Patricia Hill (COLLINS; BILGE, 2021), and how this dissemination of knowledge aims to combat the selective manner, intrinsically correlated to the phenotypical characteristics of the disseminators, a phenomenon described by Stuart Hall’s reception theory (HALL, 2003; ALEXANDER, 2009). Furthermore, through the use of digital flow control tools on social media, the regional behavioral aspects of these virtual environments will be discussed and how such regionalisms illustrate the interest of dominant groups.
Non-standard science media: How diversity can impact the vision and identification of science
Keywords: Divulgadores científicos; Antirracismo; Representatividade; Science communicators; Anti-racism; Representativeness; CIENCIAS HUMANAS::EDUCACAO